A developer's guide to cloud apps using Microsoft Azure : migrate and modernize your cloud-native applications with containers on Azure using real-world case studies /: migrate and modernize your cloud-native applications with containers on Azure using real-world case studies. (2023) - Trabelsi, Hamida Rebai
No abstract available